The effect of mutations in the envelope protein of Zika virus on cellular tropism - Ruiz Jimenez, Fernando (2022)
Zika virus infection arose as a public health issue during late 2015 and 2016 on the American continent. ZIKV epidemic was especially interesting since the previous report of patients infected by the virus only showed mild symptoms including fever, rash, and joint pain, however, the appearance of neurological symptoms including Guillain Barre syndrome in adults and microcephaly on new-borns and other clinical features that were grouped into Zika congenital syndrome. This change on the outcome of the infections resulted in many questions, what changed on the virus that favoured neuroinvasion? are these changes linked to mutations that suffered the virus? The envelope protein of the virus was the best candidate to try to explain the infection of neural cells and the later development of the reported syndromes since this is the first protein that interacts with the hosts' cells and changes in the amino acid sequence can lead to new interactions between the virus and the host.